Advanced targets preparation for TNSA laser irradiation and their characterization. (29th April 2016) - Ceccio, G.; Torrisi, L.; Cutroneo, M.
Abstract: Thin targets have been investigated at low laser intensity in order to prepare foils for TNSA (Target Normal Sheath Acceleration) laser irradiation at high intensity. Foils were prepared with different techniques, such as deposition of metallic nanoparticles on polymeric substrates. Polymer films were covered by solutions containing nanoparticles or embedded inside or covered by nanostructures. Such advanced targets permit to enhance the laser wavelength absorbance. Thick and thin targets were irradiated using laser radiation at 10 10  W/cm 2 intensity and prepared to be submitted to laser irradiation at higher intensity. The foils were characterized by optical measurements of absorbance and transmittance as a function of wavelength in the regions UV, VIS and IR. Laser irradiation measurements using a Nd:YAG laser simulate the prepulse of high laser intensity. Accelerated ions were measured with ion collectors using time of flight techniques. The protons and ions acceleration and their yields were measured as a function of the equivalent atomic number of the foils and of other characteristics, as it will be presented and discussed.